Matrix Management in Practice in Access Services at the NCSU Libraries - Harris, Colleen S. (Journal of access services, 2010)
The former Associate Head of Access and Delivery Services of the North Carolina State University Libraries reports on successful use of matrix management techniques for the Circulation and Reserves unit of the department. Despite their having fallen out of favor in much of the management literature, matrix management principles are useful for managing large access services departments involving a large staff and multiple supervisors on differing shifts. In implementing a matrix structure, the greatest challenges proved to be communication and transparency.